BRCA1/2 mutations and risk‐reducing bilateral salpingo‐oophorectomy among Latinas: The UPTAKE study. Issue 2 (3rd October 2020) - Lynce, Filipa; Schlam, Ilana; Geng, Xue; Peshkin, Beth N.; Friedman, Sue; Dutil, Julie; Nahleh, Zeina; Campos, Claudia; Ricker, Charité; Rodriguez, Patricia; Denduluri, Neelima; Ahn, Jaeil; et al.
Abstract: Bilateral salpingo‐oophorectomy (BSO) is a risk management approach with strong evidence of mortality reduction for women with germline mutations in the tumor suppressor genes BRCA1 and BRCA2 ( BRCA1/2 ). Few studies to date have evaluated uptake of BSO in women from diverse racial and ethnic backgrounds who carry BRCA1/2 mutations. The objective of the UPTAKE study was to explore rates and predictors of risk‐reducing BSO among Latinas affected and unaffected with breast cancer who had a deleterious BRCA1/2 mutation. We recruited 100 Latina women with deleterious BRCA1/2 mutations from community hospitals, academic health systems, community, and advocacy organizations. Women completed interviews in Spanish or English. We obtained copies of genetic test reports for participants who provided signed medical release. After performing threefold cross‐validation LASSO for variable selection, we used multiple logistic regression to identify demographic and clinical predictors of BSO. Among 100 participants, 68 had undergone BSO at the time of interview. Of these 68, 35 were US‐born (61% of all US‐born participants) and 33 were not (77% of the non‐US‐born participants). Among Latinas with BRCA1/2 mutations, older age (p = 0.004), personal history of breast cancer (p = 0.003), higher income (p = 0.002), and not having a full‐time job (p = 0.027) were identified as variables significantly associated with uptake of BSO. Results suggest a high rate of uptake of risk‐reducing BSO among a sample of Latinas with BRCA1/2 mutations living in the US. We document factors associated with BSO uptake in a diverse sample of women. Relevant to genetic counseling, our findings identify possible targets for supporting Latinas' decision‐making about BSO following receipt of a positive BRCA1/2 test.